Associations between ADIPOQ rs2241766 SNP and breast cancer risk: a systematic review and a meta-analysis - Xue Hu (BMC, 2021)
Abstract Purpose We aimed to conduct a meta-analysis to accurately evaluate the potential association between ADIPOQ rs2241766 gene SNP and breast cancer risk. Methods A systematic literature search on Cochrane Library, PubMed, Embase, Web of Science and China National Knowledge Infrastructure (CNKI) identified 8 articles with 1692 cases and 1890 controls. Strength of association was evaluated by pooled odds ratio (OR), 95 % confidence interval (CI) and p value. Funnel plots and Begger’s regression test were applied for testing the publication bias. Statistical analysis of all data was performed by Stata 12.0. Results The meta-analysis results indicated that the ADIPOQ rs2241766 gene polymorphism did not significantly associated with the risk of breast cancer for these genetic models (TT vs. TG + GG: OR = 1.20, 95 % CI = 0.77–1.89, p=0.417; TT + TG vs. GG: OR = 1.05, 95 % CI = 0.71–1.56, p=0.805; T vs. G: OR =1.17, 95 % CI = 0.79–1.74, p=0.437). Conclusions This study indicated that no significant relationship between the ADIPOQ rs2241766 SNP and breast cancer. Further large-scale and well-designed studies will be indispensable to confirm our result.